LEARNING TO READ AL-QUR’AN FOR ADULTS: AN ANALYSIS OF THE IMPLEMENTATION OF THE GRIYA AL-QUR’AN METHOD IN TAKLIM COUNCIL - Safi'i, Ardiyan; Mahariah, Mahariah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
For adults, the problem in reading the Qur'an is based on how to read the Qur'an and the appropriate method. This research focuses on learning to read the Qur'an for adults with the implementation of the Griya Al-Qur'an method in the taklim assembly. This research uses qualitative research methods with a phenomenological approach. This research was conducted at Taklim Council Masjid Umar bin Abdul Aziz Tembung. Through this research, it was found that the implementation of the Griya Al-Qur'an method in learning the Qur'an includes planning, implementing learning abbreviated as SUBUH (Salam, Repeat, Give, Test and Hamdalah), and evaluation in the form of oral and written tests. The obstacles to the implementation of the Griya Al-Qur'an method are internal obstacles that differ in ability and age factors. External barriers are related to activities, time and learning motivation. The solution to these obstacles is to straighten out sincere intentions, pray and make efforts before and after learning. The achievement of the Griya Al-Qur'an method based on the material is conditional, the number of participants who succeed in reading the Qur'an according to the rules and there is no punishment in learning.